Perceptions and Feedback of Undergraduate Medical Students About the Teaching and Learning Process in Pharmacology - A Question Based Study - Kumar, Rajesh; Bhat, Nusrat K (JK science : journal of medical education and research, 2021)
Integrated teaching and case-based learning has been suggested as highly significant (86%) method to improve teaching learning whereas group discussion and inclusion of multiple-choice questions (MCQs) in the examination has been advocated by 83.33% and 80.66% students respectively. Present study was carried out to evaluate student's perception and feedback regarding different teaching methodologies in pharmacology in a tertiary care teaching hospital. The Aims and Objectives of the study were to assess the effectiveness of teaching learning methodology being currently followed in pharmacology using student's feedback, to analyze the assessment mode being followed in the examination, and to analyze the student's suggestions for improving teaching and learning. Table 3 shows the students feedback about quality of teaching where 31.33% (n=47) students strongly agreed whereas 53.33% (n=80) agreed that the teaching of clinical correlation is done in pharmacology and they are very much clear to the explanation given in the class to clarify the subject. 44.66% (n=67) students agreed that useful teaching material like photographs are displayed in relation to content of lectures.